Linearized Downconverting Microwave Photonic Link Using Dual-Wavelength Phase Modulation and Optical Filtering - Bryan M. Haas; T. E. Murphy (IEEE Photonics Journal, 2011)
We describe a technique transmitting K-band microwave signals over an optical channel using electrooptic phase modulation at the transmitter followed by series phase modulation and bandpass filtering in the receiver to downconvert the transmitted signal to an intermediate frequency (IF). Unlike other downconversion methods, the method does not require a microwave mixer, high-speed optical photoreceivers, optically stabilized local oscillator, or active bias control at either phase modulator. We further show that the link can be linearized by using two wavelengths launched along orthogonal axes of a single lithium niobate phase modulator at the transmitter. We successfully demonstrate linearized downconversion of a 20-GHz microwave signal to a 250-MHz IF. The linearization method results in a 14-dB improvement in the spurious-free dynamic range compared with the nonlinearized case.